Catalytic conversion of ethane to valuable products through non-oxidative dehydrogenation and dehydroaromatization. Issue 36 (4th June 2020) - Saito, Hikaru; Sekine, Yasushi
Abstract : This review examines the catalytic ethane dehydrogenation and dehydroaromatization in terms of characteristics of active sites and their reaction mechanisms. Abstract : Chemical utilization of ethane to produce valuable chemicals has become especially attractive since the expanded utilization of shale gas in the United States and associated petroleum gas in the Middle East. Catalytic conversion to ethylene and aromatic hydrocarbons through non-oxidative dehydrogenation and dehydroaromatization of ethane (EDH and EDA) are potentially beneficial technologies because of their high selectivity to products. The former represents an attractive alternative to conventional thermal cracking of ethane. The latter can produce valuable aromatic hydrocarbons from a cheap feedstock. Nevertheless, further progress in catalytic science and technology is indispensable to implement these processes beneficially. This review summarizes progress that has been achieved with non-oxidative EDH and EDA in terms of the nature of active sites and reaction mechanisms. Briefly, platinum-, chromium- and gallium-based catalysts have been introduced mainly for EDH, including effects of carbon dioxide co-feeding. Efforts to use EDA have emphasized zinc-modified MFI zeolite catalysts. Finally, some avenues for development of catalytic science and technology for ethane conversion are summarized.